Investigating Habituation to Premonitory Urges in Behavior Therapy for Tic Disorders. Issue 6 (November 2017) - Houghton, David C.; Capriotti, Matthew R.; Scahill, Lawrence D.; Wilhelm, Sabine; Peterson, Alan L.; Walkup, John T.; Piacentini, John; Woods, Douglas W.
Abstract: Behavior therapy is effective for Persistent Tic Disorders (PTDs), but behavioral processes facilitating tic reduction are not well understood. One process, habituation, is thought to create tic reduction through decreases in premonitory urge severity. The current study tested whether premonitory urges decreased in youth with PTDs ( N = 126) and adults with PTDs ( N = 122) who participated in parallel randomized clinical trials comparing behavior therapy to psychoeducation and supportive therapy (PST). Trends in premonitory urges, tic severity, and treatment outcome were analyzed according to the predictions of a habituation model, whereby urge severity would be expected to decrease in those who responded to behavior therapy. Although adults who responded to behavior therapy showed a significant trend of declining premonitory urge severity across treatment, results failed to demonstrate that behavior therapy specifically caused changes in premonitory urge severity. In addition, reductions in premonitory urge severity in those who responded to behavior therapy were significant greater than those who did not respond to behavior therapy but no different than those who responded or did not respond to PST. Children with PTDs failed to show any significant changes in premonitory urges. Reductions in premonitory urge severity did not mediate the relationship between treatment and outcome in either adults or children. These results cast doubt on the notion that habituation is the therapeutic process underlying the effectiveness of behavior therapy, which has immediate implications for the psychoeducation and therapeutic rationale presented in clinical practice. Moreover, there may be important developmental changes in premonitory urges in PTDs, and alternative models of therapeutic change warrant investigation. Highlights: A habituation model of behavior therapy for tic disorders was tested. Reduction in premonitory urge severity was not demonstrated in children. Adult responders to behavior therapy showed declines in premonitory urge severity. Reduction in premonitory urge severity did not mediate change in treatment. Alternative models of change in behavior therapy for tics are discussed.